Medan Labuhan Shopping Center - Devin Defriza Harisdani; Aidil Fahrendy (International Journal of Architecture and Urbanism, 2018)
Medan Labuhan is one of the sub-districts that located in North Medan. The economy in this place is far left behind when compared to Medan City. To improve the economic condition of the region, it is necessary to build a shopping center. The shopping center is not only on the economic side but also a public space for people to do interaction and recreation. The analogy of Deli river into metaphor concept will make a new identity of this region. This shopping center will enhance economic growth, re-development of the historical potential of Medan Labuhan area as a new attraction for the people of Medan and tourists.